Threats in the area of security information and personal data protection and the role of Data Protection Officer in this regard - Hady-Głowiak, Stanisław; Janik, Marcin (The Opole Studies in Administration and Law, 2024)
Abstract: The article presents issues related to current threats in the area of security information and personal data protection as well as preventive measures in this area. With the above in mind, the article discusses the current system and legal solutions as well as the advisory and monitoring role of Data Protection Officer in the institution in this respect.